2013
DOI: 10.1186/1743-7075-10-35
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Lactobacillus reuteri GMNL-263 improves insulin resistance and ameliorates hepatic steatosis in high fructose-fed rats

Abstract: BackgroundType 2 diabetes mellitus (DM), characterized by peripheral insulin resistance, is the most common form of diabetes. Probiotics are live micro-organisms that, when administered in adequate amounts, confer delaying effect on DM development. In this study, the effects Lactobacillus reuteri GMNL-263 (Lr263), a new probiotic strain developed by our laboratory, on insulin resistance and the development of hepatic steatosis in high-fructose fed rats were explored. Furthermore, the relevant regulatory pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
156
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(173 citation statements)
references
References 70 publications
(73 reference statements)
9
156
3
1
Order By: Relevance
“…The results from the current study indicate that the weight gain and liver, kidney, heart and muscle weights in the HF group were significantly greater than those of control groups, despite reduced energy intake, suggesting a low energy expenditure. These results are in line with a previous study (37). Intake of sardine protein suppressed HF-diet-mediated body, liver and muscle weight gain compared with casein, which is attributable in part to the satietogenic effects of sardine protein.…”
Section: Discussionsupporting
confidence: 82%
“…The results from the current study indicate that the weight gain and liver, kidney, heart and muscle weights in the HF group were significantly greater than those of control groups, despite reduced energy intake, suggesting a low energy expenditure. These results are in line with a previous study (37). Intake of sardine protein suppressed HF-diet-mediated body, liver and muscle weight gain compared with casein, which is attributable in part to the satietogenic effects of sardine protein.…”
Section: Discussionsupporting
confidence: 82%
“…Our data showed that the fructose treatment caused significant elevation of the HbA1c levels as compared to normal salinetreated rats (Figure 8). This is in line with the previous findings that manifested positive co-relation between blood HbA1c levels and high fructose diet (Hsieh et al 2013). To the best of our knowledge, it is the first report attributing higher level of HbA1c in rats with the memory impairment.…”
Section: Discussionsupporting
confidence: 93%
“…16 Furthermore, proanthocyanidin treatment decreased the oxidative stress within the liver tissue by lowering the levels of oxidative products and oxidative-stress-induced DNA damage due to CCl 4 (Table 1 and Fig. 5), and restoring the antioxidant enzyme levels ( Table 1) that were depleted after battling against CCl 4 -mediated oxidative stress.…”
Section: Discussionmentioning
confidence: 93%